Field experimental evidence on gender discrimination in hiring: Biased as Heckman and Siegelman predicted? - Stijn Baert (Kiel Institute for the World Economy (IfW), 2015)
Correspondence studies are nowadays viewed as the most compelling avenue to test for hiring discrimination. However, these studies suffer from one fundamental methodological problem, as formulated by Heckman and Siegelman (The Urban Institute audit studies: Their methods and findings. In M. Fix, and R. Struyk (Eds.), Clear and convincing evidence: Measurement of discrimination in America, 1993), namely the bias in their results in case of group differences in the variance of unobserved determinants of hiring outcomes. In this study, the authors empirically investigate this bias in the context of gender discrimination. They do not find significant evidence for the predicted bias.
Keywords: J16; J71; M51; J41; C93; 330; correspondence experiments; gender discrimination; unobserved heterogeneity